Endoscopic submucosal dissection for hypopharyngeal cancer simultaneous with immunotherapy for renal cell carcinoma - Tatsuro Hirao; Daisuke Kikuchi; Satoshi Yamashita; Hidehiko Takeda; Kenta Watanabe; Yuji Miura; Shu Hoteya (DEN Open)
Abstract We report a case of a man who was diagnosed with superficial hypopharyngeal cancer and recurrence of renal cell carcinoma in the duodenum, liver, and gluteus medius muscle simultaneously. He underwent endoscopic submucosal dissection for hypopharyngeal cancer in parallel with systemic immunotherapy for recurrent renal cell carcinoma, resulting in completely overcoming both malignancies. Endoscopic submucosal dissection is less invasive and can be performed in a shorter duration for treating superficial hypopharyngeal cancer compared with other treatment options, such as radiation therapy, chemotherapy, and surgery. Additionally, endoscopic submucosal carcinoma is adequately effective in controlling local lesions and has a satisfactorily good prognosis.